Diverging Paths to Profitability in the Indian Cement Sector through Asset Efficiency and Capital Discipline - Chirodiya, Ashish Premjibhai (Celebes Scholar pg, 2025)
Lagos, a Nigerian state, is one of the world's most populous cities, and its transit infrastructure is under immense pressure. The state's public transportation infrastructure is grossly inadequate in suburban areas, causing traffic congestion since many residents lack access to affordable and reliable transportation. Another factor contributing to Lagos' transportation challenges is the city's socioeconomic disparities. In light of this, this study examines the transportation mobility and social equity policies in metropolitan Lagos. The study employed the interpretivist philosophy also known as qualitative or phenomenological research approach in data collection. Primary data were generated mainly through key informant interviews, while secondary data were gathered from the internet, journals, newspaper editorials, transportation policy documents, and other government publications. Key informant interviews were conducted with officers from the Lagos State Ministry of Transportation. The acquired data was analysed using a content analytic approach. Findings of the study revealed that population growth in the state's sub-urban and rural areas has put pressure on the city's infrastructure, especially its transportation system, necessitating a rethinking of transportation mobility. The study concluded that the government must invest heavily in public transport services in suburban and rural areas through public-private partnerships (PPPs) in order to improve the quality and expand the state's public transport network. The study further asserted that the state government's system of discounted fares will make transportation more affordable and accessible to low-income residents.